Driving sustainability to business success : - Pilot, M. Jayne (John Wiley&Sons, Inc, 2015)
Great leaders are those that ask questions, who are creative to drive innovation for growth of their company. The Assess-Reflect-Act section on international business principles defined in the book will ask you as the leader thought provoking questions to stimulate action within your organization to bring people, processes, and technology together for business success.Leaders need to transition to smart decisions that are data driven. The company's management system structure is important to build a strong framework for business process operations and automation for global competitiveness. Topics include: Business plans vs management systems Management system frameworks: standardization, ISO standards: Quality — ISO 9001, Environment — ISO 14001, OHSAS 18001, Integrated Management Systems Three Steps for Process Development: Identify, Insure, Improve Focus for the Organization: Compliance Costs, Best Practices, Strategic Planning Support — Resources: Innovation, Engagement, Succession Planning Data as a Valuable Resource Operation: Process Risks, Management System Control Plan, E-commerce, Enterprise Resource Planning (ERP), Green Awareness-Eco Design, Automated Controls, Cloud Computing Performance Evaluation — Monitor, Measure, Analyze, Audit, Management Review Competitive Landscape